2017
DOI: 10.1002/2017jb014060
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical behavior, failure mode, and transport properties in a porous carbonate

Abstract: We performed a systematic investigation of mechanical compaction, strain localization, and permeability in Leitha limestone. This carbonate from the area of Vienna (Austria) occurs with a broad range of grain sizes and porosity, due to changes in depositional regime and degree of cementation. Our new mechanical data revealed a simple relation between porosity and mechanical strength in both the brittle and ductile regimes. Increasing cementation and decreasing porosity led to a significant increase of the rock… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
38
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
3
3

Relationship

2
4

Authors

Journals

citations
Cited by 51 publications
(40 citation statements)
references
References 82 publications
2
38
0
Order By: Relevance
“…Taken together, the microstructural analysis of Baud et al () and our new microstructural observations (Figures ) show that grain crushing was the main micromechanism of inelastic compaction at the yield point in SML. A recent study made comparable observations in Leitha limestone of porosity between 21 and 31% and also identified grain crushing as the dominant micromechanism of inelastic compaction in the less cemented and macroporous samples (Baud et al, ). Their results were consistent with the Hertzian fracture model of Zhang et al ().…”
Section: Discussionmentioning
confidence: 69%
See 3 more Smart Citations
“…Taken together, the microstructural analysis of Baud et al () and our new microstructural observations (Figures ) show that grain crushing was the main micromechanism of inelastic compaction at the yield point in SML. A recent study made comparable observations in Leitha limestone of porosity between 21 and 31% and also identified grain crushing as the dominant micromechanism of inelastic compaction in the less cemented and macroporous samples (Baud et al, ). Their results were consistent with the Hertzian fracture model of Zhang et al ().…”
Section: Discussionmentioning
confidence: 69%
“…Our microstructural observations (Figure ) suggest that the diffuse bands could be made of several compaction band segments. SML is a weak, poorly cemented limestone and in this sense similar to the Leitha limestone in which a recent study observed compaction bands (Baud et al, ). Studying samples with different cement content, they observed that increasing cementation inhibited the development of compaction localization.…”
Section: Discussionmentioning
confidence: 72%
See 2 more Smart Citations
“…In oolithic limestones, Regnet et al (2015) demonstrated that the distribution of microporosity Journal of Geophysical Research: Solid Earth 10.1029/2018JB015636 exerts a strong influence on the macroscale mechanical behavior. Recently, Baud, Exner, et al (2017) showed the degree of cementation could also be at the origin of large variability in mechanical strength and could promote or inhibit different localized failure modes during compaction of carbonates.…”
Section: Introductionmentioning
confidence: 99%